2014
DOI: 10.1007/s00520-014-2189-0
|View full text |Cite
|
Sign up to set email alerts
|

A European patient record study on diagnosis and treatment of chemotherapy-induced anaemia

Abstract: PurposePatients with cancer frequently experience chemotherapy-induced anaemia (CIA) and iron deficiency. Erythropoiesis-stimulating agents (ESAs), iron supplementation and blood transfusions are available therapies. This study evaluated routine practice in CIA management.MethodsMedical oncologists and/or haematologists from nine European countries (n = 375) were surveyed on their last five cancer patients treated for CIA (n = 1,730). Information was collected on tests performed at diagnosis of anaemia, levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
5
23
0
1
Order By: Relevance
“…Ludwig et al estimated that at least one third of European patients had not undergone any iron status assessment at diagnosis of anemia [22]. Our own observations of the extent of iron status assessment come approximately midway between the findings of these earlier publications.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Ludwig et al estimated that at least one third of European patients had not undergone any iron status assessment at diagnosis of anemia [22]. Our own observations of the extent of iron status assessment come approximately midway between the findings of these earlier publications.…”
Section: Discussionsupporting
confidence: 50%
“…Firstly, assessments of anemia and iron status vary substantially from one country to another [22]. Secondly, medical practice has wavered over the past decade due to several changes in guidelines [15,16,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In routine practice, iron status is assessed only at low frequency [16] although assessment of haematopoiesis and iron metabolism in patients eligible for ESA therapy identified 21 % of patients to be absolute iron-deficient, defined by elevated ferritin index, and 29 % of patients to have absolute and/or functional iron deficiency, defined by elevated ferritin and/or diminished Hb content of reticulocytes, before the start of anaemia treatment [17]. Iron therapy, if given at all, is mainly based on oral iron despite that clinical studies have shown that oral iron had limited effect in ESA-treated cancer patients [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the ACT study, an Hb increase of >1 g/dl was obtained in 65% of patients [Ludwig et al 2009] [Ludwig et al 2014]. Despite the demonstration of iron deficiency in 42% of evaluated patients, iron supplementation was only used in 31% of the cases, with oral administration in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%